Influence of viscosity and chemical composition of composite resins in non-carious cervical restorations: 12-month randomized clinical trial - Matos, Thalita; Josnei de Souza, Julian; Luján Méndez Bauer, María; Núñez Aldaz, Alejandra; Jardim Frossard Duarte, Luiza; Barceleiro, Marcos; Reis, Alessandra; Dourado Loguercio, Alessandro (Brazilian Dental Science, 2021)
Objective: The objective of this double-blind, randomized controlled clinical trial was to evaluate the clinical performance of two methacrylate-based flowable composite and ormocer-based flowable composite in non-carious cervical lesions (NCCLs) of adult patients. Material and Methods: 183 restorations were performed on NCCLs using the Futurabond U adhesive system, applied in the selective enamel etching mode in all cavities. After the adhesive application, the cavities were restored with one out of the three evaluated flowable composites (n = 61 per group): ormocer-based flowable composite (Admira Fusion Flow, ORM), low viscosity methacrylate-based composite (GrandioSO Flow, LV) and high viscosity methacrylate-based composite (GrandioSO Heavy Flow, HV). After 12 months of clinical performance, these restorations were evaluated according to FDI and USPHS criteria in the following items: retention/fracture, marginal adaptation, marginal staining, postoperative sensitivity and caries recurrence. Results: eight restorations were lost/fractured after 12 months of clinical evaluation (1 in the ORM and 7 in the HV group). The retention rates for 12- months (95% confidence interval) were 98.4% (91.3%-99.7%) for the ORM group, 100% (94.5%-100%) for the LV group and 88.5% (78.1%-94.3%) for the HV group, with no statistical difference identified between any pair of groups (p > 0.05). Five restorations presented small marginal adaptation defects at the 12-months evaluation recall, and all of them were considered clinically acceptable. Conclusion: The clinical performance of the universal adhesive associated to ormocer-based or methacrylate-based flowable composite were found to be promising after 12-month of clinical evaluation. KEYWORDS Dental bonding; Dental restoration; Clinical trial.